2003
DOI: 10.1002/elps.200305545
|View full text |Cite
|
Sign up to set email alerts
|

Casein phosphoproteome: Identification of phosphoproteins by combined mass spectrometry and two‐dimensional gel electrophoresis

Abstract: We report a fast and easy-to-use procedure that combines polyacrylamide gel electrophoresis with matrix assisted laser desorption/ionization-time of flight-mass spectrometry (MALDI-TOF) and nanoelectrospray-tandem mass spectrometry (nES-MS/MS) analysis for the identification of casein components and defined phosphorylated sites. This methodology ensured identification of more than 30 phosphorylated proteins, five beta-, fifteen alpha(s1)-, ten alpha(s2)-, and four kappa-casein (CN) components, including nonall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…Effects of lipid-deprived diet on the O-glycosylation of secretory proteins The sugar motifs covalently bound to k-cas were defined in the early 1980s but the composition of the O-glycans in bovine and sheep k-cas has recently been re-visited using mass spectrometry (Mamone et al, 2003;Holland et al, 2005). The saccharides found in the antennae were essentially galactose, Lipid restriction perturbs protein O-glycosylation N-acetylgalactosamine and N-acetylneuraminic acid (in bovine: NeuAca(2-3)Galb(1-3)[NeuAca(2-6)]GalNAc).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of lipid-deprived diet on the O-glycosylation of secretory proteins The sugar motifs covalently bound to k-cas were defined in the early 1980s but the composition of the O-glycans in bovine and sheep k-cas has recently been re-visited using mass spectrometry (Mamone et al, 2003;Holland et al, 2005). The saccharides found in the antennae were essentially galactose, Lipid restriction perturbs protein O-glycosylation N-acetylgalactosamine and N-acetylneuraminic acid (in bovine: NeuAca(2-3)Galb(1-3)[NeuAca(2-6)]GalNAc).…”
Section: Discussionmentioning
confidence: 99%
“…[19] The casein fraction was dissolved in 0.4% NH 4 HCO 3 aqueous solution, pH 8.5, at a concentration of 1 µg/µl and a 20 U enzyme/mg protein ratio was used. The solution was incubated at 37…”
Section: Preparation Of Milk and Enzymatic Dephosphorylation Of Caseimentioning
confidence: 99%
“…12 Several studies have shown that in goat milk each a s2 -Cn variant can exist in two forms, identical to those described in ovine milk. For each variant, the main component corresponds to the full length of a s2 -Cn, while the minor component, originated from a skipping event, lacks the internal sequence Glu 34 -Glu 42 or Lys 35 -Glu 43 . 9 The shorter forms of a s2 -Cn variants, as those of a s1 -Cn discussed above, are named here sub-variants.…”
mentioning
confidence: 99%